2020
DOI: 10.1007/s11121-020-01095-6
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of School-Based Identification of Children and Adolescents Experiencing, or At-risk of Developing, Mental Health Difficulties: a Systematic Review

Abstract: Under-identification of mental health difficulties (MHD) in children and young people contributes to the significant unmet need for mental health care. School-based programmes have the potential to improve identification rates. This systematic review aimed to determine the feasibility of various models of school-based identification of MHD. We conducted systematic searches in Medline, Embase, PsycINFO, ERIC, British Education Index, and ASSIA using terms for mental health combined with terms for school-based i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 57 publications
5
80
0
Order By: Relevance
“…Although there have been calls for the introduction of school-based universal screening in the UK as a strategy for enhancing the prevention of mental health problems and narrowing the treatment gap (Humphrey & Wigelsworth, 2016;Williams, 2013a, Williams, 2013b, there is a lack of published research evaluating the effectiveness of this approach in a UK context (Anderson et al, 2018). Furthermore, there is a lack of evidence on the acceptability and feasibility of school-based identification methods (Soneson et al, 2020).…”
Section: Evidence On Systematic School-based Methods Of Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been calls for the introduction of school-based universal screening in the UK as a strategy for enhancing the prevention of mental health problems and narrowing the treatment gap (Humphrey & Wigelsworth, 2016;Williams, 2013a, Williams, 2013b, there is a lack of published research evaluating the effectiveness of this approach in a UK context (Anderson et al, 2018). Furthermore, there is a lack of evidence on the acceptability and feasibility of school-based identification methods (Soneson et al, 2020).…”
Section: Evidence On Systematic School-based Methods Of Identificationmentioning
confidence: 99%
“…Despite the clear importance of, and recent policy focus on the early identification of MHDs, there is a paucity of evidence on the effectiveness, feasibility, and acceptability of school-based identification models, especially within the UK and in primary schools settings (Anderson et al, 2018;Fazel et al, 2014;Humphrey & Wigelsworth, 2016;Soneson et al, 2020). The current study aimed to explore the 'in principle' acceptability of four key methods of identification from key stakeholders in primary/elementary schools using qualitative methods.…”
Section: Current Studymentioning
confidence: 99%
“…These findings were in line with evidence from a systematic review of the feasibility of school-based identification of young people experiencing or at-risk of developing mental health difficulties, which also found cost, time, resources and obtaining consent were common barriers. 26 It is important to note that in-person screening was more successful than postal screening; this may reflect the younger age of those contacted via postal screening, although the stark difference suggests this is not the case. Interestingly, our findings did support previous research 5 that suggested it was more common to have mood difficulties without weight problems than it was to have weight problems without low mood.…”
Section: Discussionmentioning
confidence: 99%
“…We highlight additional steps we have taken and describe how our methodology deviated from the original Arksey's and O'Malley's framework (8) to aid the pragmatic purpose of our SLR. This paper focuses only on methodological aspects of the SLR; ndings from the review are published elsewhere (17)(18)(19).…”
Section: Nonementioning
confidence: 99%